Influenza vaccine effectiveness among high-risk groups: A systematic literature review and meta-analysis of case-control and cohort studies - Vincenzo Restivo; Claudio Costantino; Stefania Bono; Marialuisa Maniglia; Valentina Marchese; Gianmarco Ventura; Alessandra Casuccio; Fabio Tramuto; Francesco Vitale (Taylor & Francis Group, 2018)
Vaccination represents the most effective intervention to prevent infection, hospitalization and mortality due to influenza. This meta-analysis quantifies data reporting influenza vaccine effectiveness (VE) on influenza visits and hospitalizations of case-control and cohort studies among high-risk groups. A systematic literature review including original articles published between 2007 and 2016, using a protocol registered on Prospero with No. 42017054854, and a meta-analysis were conducted. For 3 high-risk groups (subjects with underlying health conditions, pregnant women and health care workers) only a qualitative evaluation was performed. The VE quantitative analysis demonstrated a clear significant overall effect of 39% (95%CI: 32-46%) for visits and 57% (95%CI: 30-74%) for hospitalization among children. Considering the elderly influenza VE had a clear effect of 25% (95%CI: 6-40%) for visits and 14% (95%CI: 7-21%; p<0.001) for hospitalization. This study showed the high VE of influenza vaccination among high-risk groups, representing a tool for public health decision-makers to develop evidence-based preventive interventions to avoid influenza outcomes.